Shedding Light on the Molecular Recognition of Sub-Kilodalton Macrocyclic Peptides on Thrombin by Supervised Molecular Dynamics - Hassankalhori, Mahdi; Bolcato, Giovanni; Bissaro, Maicol; Sturlese, Mattia; Moro, Stefano (Frontiers in Molecular Biosciences, 2021)
Macrocycles are attractive structures for drug development due to their favorable structural features, potential in binding to targets with flat featureless surfaces, as well as their ability to disrupt protein-protein interactions. Moreover, large novel highly diverse libraries of low molecular weight macrocycles with therapeutically favorable characteristics have been recently established. Considering the mentioned facts, having a validated fast, and accurate computational protocol for studying the molecular recognition and binding mode of this interesting new class of macrocyclic peptides deemed to be helpful as well as insightful in the quest of accelerating drug discovery. To that end, the ability of the in-house supervised molecular dynamics protocol called SuMD in the reproduction of X-ray crystallography final binding state of a macrocyclic non-canonical tetrapeptide—from a novel library of 8988 sub-kilodalton macrocyclic peptides—in thrombin active site was successfully validated. A comparable binding mode with the minimum root-mean-square deviation (RMSD) of 1.4 Å at simulation time point 71.6 nanoseconds was achieved. This method validation study extended the application domain of SuMD sampling method for computationally cheap, fast but accurate, and insightful macrocycle-protein molecular recognition studies.